Prospects of Long Term Relapse after Management of Pediatric Clubfoot with the Ponseti Method: A Systematic Review - Julia Nguyen BS; Aedan Hanna; Jacob Veliky BS; Jae Hoon Choi; Dhvani Shihora; Aleksandra McGrath; Neil Kaushal; Folorunsho Edobor-Osula MD; Alice Chu (Foot & Ankle Orthopaedics, 2022)
Category: Other; Ankle; Hindfoot; Midfoot/Forefoot Introduction/Purpose: The Ponseti method of serial casting has been recognized as the gold standard for management of idiopathic clubfoot, a very common congenital foot deformity. While the short to midterm success of the method has been widely confirmed in the literature, there are very limited published studies of the longer term trend of relapse. Dr. Ponseti's own definitive assessment of the long term result has not been decisively reevaluated by the literature. This systematic review examines the long-term functional outcomes and evaluates the relapse rates of the Ponseti method. Methods: A comprehensive search was conducted of PubMed, CINAHL, Web of Science, and Cochrane from inception to December 2020 to identify literature on clubfoot. Using PRISMA guidelines, the search terms clubfoot OR clubfeet OR clubbed foot OR clubbed feet OR talipes equinovarus were used. Articles containing more than three human subjects, were included. The database was searched for longitudinal studies of pediatric, idiopathic clubfoot management with the Ponseti method. Retrospective studies of primary Ponseti management performed on neonates and children up to twenty four months old and with reported mean follow-up of two years or longer were included. Evaluation reported according to different scoring systems based on clinical examination of foot function, radiographic studies, or patient satisfaction questionnaires were dichotomized as success (good to satisfactory results) or failure (residual or relapse that requires corrective management or surgery). Probability of less than 0.05 is considered statistically significant. Results: The search yielded 20 articles following 2782 treated idiopathic clubfeet for 6.4 (2.6 - 19) years. The rate of successful initial correction was 97% (86.6% - 100%), satisfactory functional outcomes at last follow-up was 90% (63.4% - 100%), relapse was 21% (5.3% - 68%), and surgery needed to correct relapse was 9% (2.5% - 24%). Functional outcomes were inversely correlated with follow-up to 9 years (R= -0.5300, p= 0.0173), then became insignificantly associated when following up to 19 years (R= - 0.2480, p= 0.1458). Relapse rate was strongly correlated with follow-up to 9 years (R= 0.5540, p= 0.0129), then subsided thereafter to 19 years (R= 0.3792, p= 0.0495). The frequency of surgical release correlated with follow-up in a similar pattern, strongly up to 9 years (R= 0.6204, p= 0.0052), subsiding thereafter to 19 years (R= 0.3142, p= 0.0887). Conclusion: The short-term trends were consistent with literature findings that the rate of relapse increased during the first ten years, leading to lower patient satisfaction and higher rate of surgical correction. However, our new findings of weak long-term correlation and declining deformity relapse after nine years supported Dr. Ponseti's own assessment that late relapses were exceptions. The trend was consistent with uncommon returning relapses after a secondary corrective management or surgery. This trend also supports the postulation that the cause of relapse was non-compliance with foot abduction bracing, rather than clinicians' learning curves, age at presentation, or deformity severity.